Indicaciones no tradicionales de amigdalectomía. Actualización - Contreras R., Pilar; Nazar S., Rodolfo (Revista Hospital Clínico Universidad de Chile, 2014)
Tonsillectomy is the most common surgical procedure in ENT surgery. Indications are well known in the field. Upper airway obstruction caused by tonsilar hyperplasia and recurrent bacterial infections are the most frecuent indications of tonsillectomy, however there are many other pathologies where tonsillectomy is considered part of the treatment. Non traditional indications, include IgA nephropathy, pediatric autoinmune neuropsychiatric disorders associated with Streptococcus, periodic fever with aphtous stomatitis, pharyngitis and adenitis, some dermatologic entities, among others. In this review we compile recent scientific evidence supporting the non tradicional indications of tonsillectomy, in order to allow an informed decision when prescribing this surgical procedure for the treatment of entities which are not of high prevalence in the daily practice. Evidence supports tonsillectomy as part of the treatment of some deseases, such as IgA nephropathy, however further evidence is required to support this treatment for the other pathologies.